Enhanced flexibility and electron-beam-controlled shape recovery in alumina-coated Au and Ag core–shell nanowires. (23rd November 2017) - Vlassov, Sergei; Polyakov, Boris; Vahtrus, Mikk; Mets, Magnus; Antsov, Mikk; Oras, Sven; Tarre, Aivar; Arroval, Tõnis; Lõhmus, Rünno; Aarik, Jaan
Abstract: The proper choice of coating materials and methods in core–shell nanowire (NW) engineering is crucial to assuring improved characteristics or even new functionalities of the resulting composite structures. In this paper, we have reported electron-beam-induced reversible elastic-to-plastic transition in Ag/Al2 O3 and Au/Al2 O3 NWs prepared by the coating of Ag and Au NWs with Al2 O3 by low-temperature atomic layer deposition. The observed phenomenon enabled freezing the bent core–shell NW at any arbitrary curvature below the yield strength of the materials and later restoring its initially straight profile by irradiating the NW with electrons. In addition, we demonstrated that the coating efficiently protects the core material from fracture and plastic yield, allowing it to withstand significantly higher deformations and stresses in comparison to uncoated NW.